THE EFFECTIVENESS OF USING DUOLINGO APPLICATION TO IMPROVE STUDENTS VOCABULARY - lina faiqotul himmah (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
English is an international language in Indonesia. Many students have difficulty in English subjects. So learning vocabulary is an important part of learning English. This research aims to improve the English vocabulary mastery of class VIII students at Mandala Jetis Junior High School through the application of the Duolingo media application. The type of research is quantitative. The population is class VIII students of Mandala Jetis Junior High School for the 2022-2023 academic year. This research uses a sampling method, namely a saturated sample or census. So there were 22 students who were all class VIII students at Mandala Jetis Junior High School. The pre-test and post-test containing multiple choices were applied to class VIII students at Mandala Jetis Junior High School. Data analysis includes instrumental tests using validity and reliability tests, normality tests, paired sample t tests. The results of statistical analysis using SPSS show that the calculated t value is 3.634 > from the t table 1.721 with a significance value of 0.002 < 0.05. So it can be stated that there is a significant difference in students' vocabulary mastery before and after using the Duolingo application in class VIII of Mandala Jetis Junior High School.